The Relationship Between Behavioural and Neoclassical Economic - Paula-Elena Diacon; Madalina Calance (CES Working Papers, 2014)
The purpose of this article is to analyze the relationship between the discipline of Behavioural Economics and the Neoclassical School. On the basis of the available literature, the paper aims to investigate if the two branches are totally opposite, or if the behavioural theories only extend and complement the mainstream economics.
Keywords: D01; D03; 330; behavioural economics; mainstream economics; economic behaviour